Nutraceutical potential of traditional fermented soybean (Hawaijar): Nutraceutical potential of traditional fermented soybean (Hawaijar) - LOITONGBAM SOPHIA DEVI; HEISNAM NANITA DEVI; NILIMA KARAM; TOIJAM SUNANDA DEVI (Journal of Oilseeds Research, 2023)
Fermentation not only reduces the toxins but also it is an excellent processing method for improving nutritional and functional properties of soybean due to the increased content of small bioactive compounds. The NEH region of India also has similar traditional fermented soy products. ACE inhibitory activity was found to increase during fermentation and exhibited higher ACE inhibition percent in starter culture strain (H) than starter culture strain (S) of both the soybean used (local small variety and JS-335). Fermentation of soybean with different micro-organisms improve the bio-functional properties due to the increase in free isoflavones and peptides.